CHILD RIGHTS IN INDIA : LAW,POLICY,AND PRACTICE - ASHA BAJPAI (NEW DELHI OXFORD UNIVERSITY PRESS, 2017)
This work analyses the laws in the light of court judgments and policy initiatives taken in India. It also examines the interventions and strategies employed by non-governmental organizations in recommending legislative reforms in support of children.
Keywords: CHILDREN'S RIGHTS